2014
DOI: 10.1242/dev.100347
|View full text |Cite
|
Sign up to set email alerts
|

Targeted transgene integration overcomes variability of position effects in zebrafish

Abstract: Zebrafish transgenesis is increasingly popular owing to the optical transparency and external development of embryos, which provide a scalable vertebrate model for in vivo experimentation. The ability to express transgenes in a tightly controlled spatio-temporal pattern is an important prerequisite for exploitation of zebrafish in a wide range of biomedical applications. However, conventional transgenesis methods are plagued by position effects: the regulatory environment of genomic integration sites leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 73 publications
0
67
0
Order By: Relevance
“…However, the possible position effects of transgene integration on influencing GCaMP6s expression in these two transgenic lines should also be considered. Indeed, previous studies in mouse and zebrafish suggested that expression pattern of a gene inserted at the transgene integration locus may be influenced by the nearby regulatory elements (Jaenisch et al, 1981; Roberts et al, 2014; Wilson et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…However, the possible position effects of transgene integration on influencing GCaMP6s expression in these two transgenic lines should also be considered. Indeed, previous studies in mouse and zebrafish suggested that expression pattern of a gene inserted at the transgene integration locus may be influenced by the nearby regulatory elements (Jaenisch et al, 1981; Roberts et al, 2014; Wilson et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Together with site-specific transgenesis using PhiC31 (Roberts et al, 2014), Cre- loxP (Lin et al, 2013), the Gal4/UAS system (Halpern et al, 2008) and a range of inducible systems that are amenable for use in the model, these genomic engineering tools will accelerate the development of MND models in the zebrafish.…”
Section: The Zebrafish Toolbox: How Useful Is It For Studying Mnds?mentioning
confidence: 99%
“…Recently, site-specific integration has been achieved in model fish using PhiC31 integrase or genome-editing technology [47][48][49], which would avoid nontarget effects that usually occur in fish with randomly integrated transgenes. So far, however, no ideal integration sites, like ROSA26 in mice and humans, have been found in fish.…”
Section: Discussionmentioning
confidence: 99%